Pathologic Findings in Fatal and Nonfatal Asthma. Issue 4 (December 2013) - Wright, Joanne L.; Churg, Andrew M.
Asthma is a common disease in the population and fatal asthma cases are not rare. Patients with fatal asthma not infrequently die outside of hospitals and become forensic cases. The pathologic features of asthma are very variable, but fatal asthma is always characterized by extensive mucous plugs in the airways and lungs that tend to remain inflated when the chest is opened. Other microscopic features that may be seen in asthma include increased amounts of airway smooth muscle, marked thickening of airway basement membranes, goblet cell hyperplasia, and various patterns of airway inflammation including eosinophils, neutrophils, and lymphocytes. Absent a history, a presumptive diagnosis of fatal asthma can be made in a patient whose lungs are hyperinflated and demonstrate numerous mucous plugs in the large airways, and this is usually accompanied by a markedly thickened basement membrane in the large airways on microscopic examination, but the possibility that the fatal asthma attack was precipitated by exogeneous factors such as drugs, fumes, or irritants should be borne in mind.